Severity of Insomnia Symptoms in Young Adults - Saini, Satvinder Singh; Sharma, Nov Rattan (Asian Journal of Interdisciplinary Research, 2023)
Insomnia is characterized by difficulty in falling and/or staying asleep. People with insomnia experience one or more of the following symptoms: difficulty getting asleep, difficulty falling asleep again frequently throughout the night and after being awake for a while, and waking up too early or unintentionally in the morning. Objective: To study the severity of insomnia symptoms in young adults. Design: It was a cross-sectional single group exploratory study. Participants: A sample of hundred participants of both genders (53 males and 47 females) aged between 20 to 30 years was taken. Procedure: An online survey was conducted by using ‘Google Forms’ to study Insomnia symptoms among young adults in India. Results: About 52% of total participants reported one or more symptoms of insomnia, and 12% reported moderate level, 14% reported severe level and 26% reported sub-threshold level of insomnia symptoms. A Chi-square analysis of frequency distribution confirmed the significant difference among the four groups; namely no insomnia (n=48), sub-threshold insomnia (n=26), moderate level insomnia (n=12), and severe level of insomnia (n=14) at χ2 (3, N=100) = 32.8, p >0.0001. Conclusion: A large proportion of young adults reported insomnia symptoms. There is a dire need to address this serious issue.